Puréed Foods and Fiber - Wendy J. Dahl (EDIS)
People with swallowing problems who require a puréed diet may not meet their recommended intake of fiber. But puréed diets can be planned to achieve fiber recommendations by choosing higher-fiber puréed foods often. And a variety of fiber ingredients are available that can be added to puréed foods. This 4-page fact sheet was written by Wendy J. Dahl and published by the UF Department of Food Science and Human Nutrition, January 2013.